From Sakhawat Memorial School to Rokeya Hall: A Journey Towards Language as Self-Respect - Gupta, Kolkata, India, Sarmistha Dutta (Asiatic: IIUM Journal of English Language and Literature, 2013)
The paper traces the trajectory of Sakhawat Memorial School â€“ founded in Calcutta by Rokeya Sakhawat Hossain in 1911 â€“ with reference to questions of identity and language in undivided India. The secularist Rokeya prioritised her ethno-linguistic identity as against her pan-Islamist self in the running of her school at a time when respectable Muslims of Bengal were caught between choosing the â€œIslamicâ€ Urdu and â€œHinduâ€ Bengali as their mother tongue. Did the pioneering efforts of Sakhawat Memorial School in making Bengali Muslim women learn to read and write in their mother tongue have anything to do with the coming together of all Bengalis and womenâ€™s contribution in upholding the honour and dignity of their mother tongue during the Language Movement of 1952 in erstwhile East Pakistan? In addressing this question, the paper seeks to recognise Rokeya and the Sakhawat Memorial School as precursors of the secular nationalist movement that saw the birth of a new nation in 1971.